Mediation Effect of Assessment as Learning in Mobile-Based Module on Vocational Education Student’s HOTS - Fitrah Asma Darmawan; Amat Jaedun (Universitas Negeri Makassar, 2020)
This study aims to find out the mediation effect of assessment as learning (AaS) model in a mobile-based module upon students’ higher-order thinking. This study is a Research and Development (R & D) and Experimental research. R&D method consisted of: information gathering, product planning, product development, product validation, preliminary test, limited trial, revision, product implementation, and dissemination. The experimental method was one-group time-series design. Data is gathered by using the online assessment sheets. This study employed 40 students of vocational high school. The interpretation of higher-order thinking improvement is based on the criteria of value gain. In addition to calculating the gain score, this study uses a hypothesis. The hypothesis is tested by comparative two samples technique. The result shows that assessment as learning model in mobile-based module has improved student’s higher order thinking skills. The teacher needs to consider the use of the assessment as learning model on the learning module.